Synthesis of Mo4O11@MoO3 nanobelts and their improved sensing performance to NO2 gas. (22nd February 2019) - Li, Yixue; Song, Zhongxiao; Li, Yanhuai; Li, Sha; Wang, Hairong; Song, Baorui; Gao, Bo; Du, Xiaoye
Abstract: In the present work, Mo4 O11 @MoO3 nanobelts are successfully prepared by a two-step hydrothermal method. The nanobelts are about several micrometers in length and 200–300 nm in width with Mo4 O11 nanoparticle on surface. The introduction of nanoparticles act as the adsorption sites which facilitate the adsorption of O2 and NO2 gas molecules, because of the point defects such as Mo 5+ ions and oxygen vacancies inducing to increase the concentration of carriers, which synthetically contribute the sensing performance enhancement. The Mo4 O11 @MoO3 nanobelts show excellent sensing performance with 6 times enhancement with the decreased working temperature comparing with the pure α -MoO3 nanobelts. This study indicate that this kind of sensor show a promising application in NO2 detection.